The Effect of Education on the Identification of Pulmonary TB Case Findings in the Post-Covid-19 Era at Dukuh Kupang Public Health Center Surabaya: Original Research - Rusdi, Muhammad Salsabeela; Rusdi, Warda Elmaida; Farindra, Irmawan; Artanti, Widyana Beta; Fahira, Aulia; Affrita, Tia Maya; Hanum, Laila (Faculty of Medical - UPN Veteran Jawa Timur, 2025)
Indonesia is one of the countries affected by the COVID-19 pandemic. In the era of the COVID-19 pandemic, Tuberculosis disease is no longer in focus because the COVID-19 pandemic is the focus of the main problem. TB is one of the diseases that causes death in the world caused by bacterial infection Mycobacterium tuberculosis. TB in the pandemic era is very difficult to diagnose because the diagnosis of respiratory disease is directed at COVID-19 disease. Based on this, this study was conducted with the aim of knowing the impact of the COVID-19 pandemic on the findings of TB cases. The study was conducted using a cross-sectional observational analytic method at the Dukuh Kupang Community Health Center, Surabaya. The results showed a decrease in the number of pulmonary TB cases in recent years. This decrease is due to a decrease in screening and diagnosis of suspected TB, as well as an increase in better understanding in the community regarding the difference in symptoms of COVID-19 and TB and a decrease in the examination of TB sputum samples.